Financing of CPEC Projects: Implications for Pakistan - Sharif, Salman (Journal of Public Policy Practitioners, 2022)
The China-Pakistan Economic Corridor (CPEC), termed the game changer, has galvanised the strong fraternal bonds between Pakistan and China into a shared economic future. It would link China’s western region of Xinjiang to Pakistan through Karakoram crossings, traversing Gilgit Baltistan (GB) through Khyber Pakhtunkhwa, Punjab, Sindh, and all the way to Gwadar in Balochistan at Pakistan’s South Western coastline. The projects envisaged under CPEC are estimated to be worth US$ 62 billion including energy projects, railway lines, and road networks with the Gwadar port as the culmination point. Several other projects, such as Special Economic Zones (SEZs), knowledge exchanges, and optic fibre network are also part of CPEC. Financing all the CPEC projects, planned between 2015-2030, would be a huge undertaking for Pakistan’s feeble and traumatised economy. Despite offering great opportunities for Pakistan, CPEC also faces criticism on account of its financial sustainability and lack of transparency, with fears that it may lead Pakistan into a Chinese “debt trap”. The current research examined whether the issues related to financing of CPEC could outweigh its socio-economic benefits to Pakistan’s economy. While there may be no “debt trap” for Pakistan from CPEC, however, Pakistan needs concrete policy measures to ensure the best use of this opportunity in order to build its infrastructure and human capital and ensure repayment of direct loan of US$ 5.8 billion to be paid off by 2035. . This paper offers several policy recommendations pertaining to regular follow-up of progress at leadership level, pursuing regional integration to expand CPEC to Afghanistan and Central Asia, macroeconomic reforms to stabilize the economy, use of innovative methods to manage CPEC debt, and liabilities, capacity building and technology transfer, capitalization on industrial development through SEZs, early implementation of ML-1, and inclusion of Diamer Bhasha dam in CPEC.